Temperature-dependent transformation and solubility of trace metals in palm kernel shell ash - Satoshi Takeuchi; Kosei Yamashita; Yohey Hashimoto (Biomass and Bioenergy, 2026)

Emerging threats from climate change on our oceans demand proactive action - Jim Falk; Swadhin Behera; Nancy Bermas; Tony Capon; Joachim von Braun; Rita R. Colwell; Adel S. El-Beltagy; Richard Damania; Charles F. Kennel; Margaret Leinen; Phoebe Koundouri; Cherry A. Murray; et al. (Sustainability Science, 2025)

Three-dimensional textures of Ryugu samples and their implications for the evolution of aqueous alteration in the Ryugu parent body - Akira Tsuchiyama; Megumi Matsumoto; Junya Matsuno; Masahiro Yasutake; Tomoki Nakamura; Takaaki Noguchi; Akira Miyake; Kentaro Uesugi; Akihisa Takeuchi; Shota Okumura; Yuri Fujioka; Mingqi Sun; et al. (Geochimica et Cosmochimica Acta, 2024)

Polyglucuronic acids prepared from α-(1 → 3)-glucan by TEMPO-catalytic oxidation - Korawit Chitbanyong; Gaoyuan Hou; Izumi Shibata; Miyuki Takeuchi; Satoshi Kimura; Akira Isogai (Carbohydrate Polymers, 2024)

Survey and risk assessment of aflatoxins and sterigmatocystin in Japanese staple food items and the evaluation of an in-house ELISA technique for rapid screening - Tomoya Yoshinari; Yoshiko Sugita-Konishi; Eiko Sato; Hiroshi Takeuchi; Masaru Taniguchi; Toru Fukumitsu; Akira Shimoyama; Ayumu Nakamura; Satoshi Murayama; Shinji Owaki; Shiro Miyake; Yukiko Hara-Kudo (Food Control, 2024)

Effect of degree of substitution on the microphase separation and mechanical properties of cellooligosaccharide acetate-based elastomers - Satoshi Katsuhara; Naoki Sunagawa; Kiyohiko Igarashi; Yutaka Takeuchi; Kenji Takahashi; Takuya Yamamoto; Feng Li; Kenji Tajima; Takuya Isono; Toshifumi Satoh (Carbohydrate Polymers, 2023)

Nonequilibrium spherulitic magnetite in the Ryugu samples - Elena Dobrică; Hope A. Ishii; John P. Bradley; Kenta Ohtaki; Adrian J. Brearley; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; Mitsutaka Haruta; Hikaru Saito; Satoshi Hata; et al. (Geochimica et Cosmochimica Acta, 2023)

Evaluating inaccurate pollen concentrations caused by turbulence using passive sampler - Kenji Miki; Shigeto Kawashima; Satoshi Kobayashi; Shinji Takeuchi; Yi-Ting Tseng; Kimihito Nakamura (Aerobiologia, 2022)

Effect of short- and long-term melatonin treatments on the reproductive activity of the tropical damselfish Chrysiptera cyanea - Satoshi Imamura; Sung-Pyo Hur; Yuki Takeuchi; Muhammad Badruzzaman; Angka Mahardini; Dinda Rizky; Akihiro Takemura (Fish Physiology and Biochemistry, 2022)

Kruppel-like factor 4 upregulates matrix metalloproteinase 13 expression in chondrocytes via mRNA stabilization - Yuto Takeuchi; Sayuri Tatsuta; Akiyoshi Kito; Junji Fujikawa; Shousaku Itoh; Yuki Itoh; Shigehisa Akiyama; Takashi Yamashiro; Satoshi Wakisaka; Makoto Abe (Cell and Tissue Research, 2020)

The mRNA expression patterns of kisspeptins, GnRHs, and gonadotropins in the brain and pituitary gland of a tropical damselfish, Chrysiptera cyanea, during the reproductive cycle - Satoshi Imamura; Sung-Pyo Hur; Yuki Takeuchi; Muhammad Badruzzaman; Angka Mahardini; Dinda Rizky; Akihiro Takemura (Fish Physiology and Biochemistry, 2020)

Why does the Quiet Eye improve aiming accuracy? Testing a motor preparation hypothesis with brain potential - Yuuki Mizusaki; Sachi Ikudome; Yasumitsu Ishii; Satoshi Unenaka; Taishi Funo; Tatsuya Takeuchi; Kisho Ogasa; Shiro Mori; Hiroki Nakamoto (Cognitive Processing, 2019)

Differential determination of plasticizers and organophosphorus flame retardants in residential indoor air in Japan - Shinji Takeuchi; Toshiko Tanaka-Kagawa; Ikue Saito; Hiroyuki Kojima; Kazuo Jin; Masayuki Satoh; Satoshi Kobayashi; Hideto Jinno (Environmental Science and Pollution Research, 2018)

Kruppel-like factor 4 regulates matrix metalloproteinase and aggrecanase gene expression in chondrocytes - Junji Fujikawa; Yuto Takeuchi; Satoshi Kanazawa; Ahmed G. Nomir; Akiyoshi Kito; Eman Elkhashab; Amr M. Ghaleb; Vincent W. Yang; Shigehisa Akiyama; Ichijiro Morisaki; Takashi Yamashiro; Satoshi Wakisaka; et al. (Cell and Tissue Research, 2017)

Screening of rice mutants with improved saccharification efficiency results in the identification of CONSTITUTIVE PHOTOMORPHOGENIC 1 and GOLD HULL AND INTERNODE 1 - Ko Hirano; Reiko Masuda; Wakana Takase; Yoichi Morinaka; Mayuko Kawamura; Yoshinobu Takeuchi; Hiroki Takagi; Hiroki Yaegashi; Satoshi Natsume; Ryohei Terauchi; Toshihisa Kotake; Yasuyuki Matsushita; et al. (Planta, 2017)

First report of phytophthora rot on Wasabia japonica caused by Phytophthora drechsleri in Japan - Ayaka Minoshima; Jun Takeuchi; Tsuyoshi Ono; Satoshi Kagiwada; Hiromichi Horie; Yuuri Hirooka (Journal of General Plant Pathology, 2017)

Effects of neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) treatment on ovarian development of the sapphire devil, Chrysiptera cyanea - Muhammad Badruzzaman; Satoshi Imamura; Yuki Takeuchi; Taro Ikegami; Akihiro Takemura (Fish Physiology and Biochemistry, 2015)

Kruppel-like factor 4 expression in osteoblasts represses osteoblast-dependent osteoclast maturation - Junji Fujikawa; Mariko Tanaka; Shousaku Itoh; Toshiya Fukushi; Kojiro Kurisu; Yuto Takeuchi; Ichijiro Morisaki; Satoshi Wakisaka; Makoto Abe (Cell and Tissue Research, 2014)

The nitrogen cycle in cryoconites: naturally occurring nitrification‐denitrification granules on a glacier - Takahiro Segawa; Satoshi Ishii; Nobuhito Ohte; Ayumi Akiyoshi; Akinori Yamada; Fumito Maruyama; Zhongqin Li; Yuichi Hongoh; Nozomu Takeuchi (Environmental Microbiology, 2014)
Summary Cryoconites are microbial aggregates commonly found on glacier surfaces where they tend to take spherical, granular forms. While it has been postulated that the microbes in cryoconite granules play an important role in glacier ecosystems, information on their community structure is still limited, and their functions remain unclear. Here, we present evidence for the occurrence of nitrogen cycling in cryoconite granules on a glacier in C entral A sia. We detected marker genes for nitrogen fixation, nitrification and denitrification in cryoconite granules by digital polymerase chain reaction ( PCR ), while digital reverse transcription PCR analysis revealed that only marker genes for nitrification and denitrification were abundantly transcribed. Analysis of isotope ratios also indicated the occurrence of nitrification; nitrate in the meltwater on the glacier surface was of biological origin, while nitrate in the snow was of atmospheric origin. The predominant nitrifiers on this glacier belonged to the order Nitrosomonadales , as suggested by amoA sequences and 16S ribosomal RNA pyrosequencing analysis. Our results suggest that the intense carbon and nitrogen cycles by nitrifiers, denitrifiers and cyanobacteria support abundant and active microbes on the A sian glacier.

Enhancement of Saccharina kelp production by nutrient supply in the Sea of Japan off southwestern Hokkaido, Japan - Yukio Agatsuma; Hikaru Endo; Shigeki Yoshida; Chikara Ikemori; Yoshio Takeuchi; Hiroaki Fujishima; Kazuhiko Nakajima; Mitsuhiro Sano; Nobuyuki Kanezaki; Hisaeki Imai; Naoki Yamamoto; Hiroki Kanahama; et al. (Journal of Applied Phycology, 2014)

Comparison of expression and enzymatic properties of Aspergillus oryzae lysine aminopeptidases ApsA and ApsB - Junichiro Marui; Mayumi Matsushita-Morita; Sawaki Tada; Ryota Hattori; Satoshi Suzuki; Hitoshi Amano; Hiroki Ishida; Youhei Yamagata; Michio Takeuchi; Ken-Ichi Kusumoto (World Journal of Microbiology and Biotechnology, 2012)

Improvement in the feeding activity, early growth and survival of Pacific bluefin tuna Thunnus orientalis larvae fed a casein peptide-based microdiet supplemented with inosine monophosphate - Yutaka Haga; Toshihito Naiki; Youhei Tazaki; Takaaki Shirai; Yusuke Takaki; Yosuke Tanaka; Kazunori Kumon; Satoshi Shiozawa; Shukei Masuma; Toshihiro Nakamura; Shuzo Ishida; Toshio Takeuchi (Fisheries Science, 2011)

Overexpression and Characterization of an Extracellular Leucine Aminopeptidase from Aspergillus oryzae - Mayumi Matsushita-Morita; Sawaki Tada; Satoshi Suzuki; Ryota Hattori; Junichiro Marui; Ikuyo Furukawa; Youhei Yamagata; Hitoshi Amano; Hiroki Ishida; Michio Takeuchi; Yutaka Kashiwagi; Ken-Ichi Kusumoto (Current Microbiology, 2011)

Object orientation in two dimensional grasp with friction towards minimization of gripping power - Satoshi Ito; Shouta Takeuchi; Minoru Sasaki (Biological Cybernetics, 2009)

Prediction of birch airborne pollen counts by examining male catkin numbers in Hokkaido, northern Japan - Michiyasu Yasaka; Satoshi Kobayashi; Shinji Takeuchi; Sawako Tokuda; Mika Takiya; Yasuyuki Ohno (Aerobiologia, 2009)

Effect of seawater temperature on the productivity of Laminaria japonica in the Uwa Sea, southern Japan - Satoshi Suzuki; Kazushige Furuya; Tadashi Kawai; Ichiro Takeuchi (Journal of Applied Phycology, 2008)

Effects of ultraviolet-B irradiation on the cuticular wax of cucumber (Cucumis sativus) cotyledons - Satoshi Fukuda; Atsushi Satoh; Hirokazu Kasahara; Hidetoshi Matsuyama; Yuichi Takeuchi (Journal of Plant Research, 2008)

Conformational change in the active center region of GST P1-1, due to binding of a synthetic conjugate of DXR with GSH, enhanced JNK-mediated apoptosis - Tadashi Asakura; Atsuko Sasagawa; Hitoshi Takeuchi; Shun-ichi Shibata; Hideki Marushima; Satoshi Mamori; Kiyoshi Ohkawa (Apoptosis, 2007)

The effect of body size on mating system and parental roles in a biparental cichlid fish (Julidochromis transcriptus): a preliminary laboratory experiment - Satoshi Awata; Hideaki Takeuchi; Masanori Kohda (Journal of Ethology, 2006)

The effect of body size on mating system and parental roles in a biparental cichlid fish (Julidochromis transcriptus): a preliminary laboratory experiment - Satoshi Awata; Hideaki Takeuchi; Masanori Kohda (Journal of Ethology, 2006)